2020
DOI: 10.15520/jcmro.v3i08.323
|View full text |Cite
|
Sign up to set email alerts
|

Laser and its Implications in Dentistry : A Review Article

Abstract: The term LASER is an acronym for ‘Light Amplification by the Stimulated Emission of Radiation’. Miaman was the first who introduced laser application in dentistry in 1960 and its hard and soft tissue application. There is lot of advancement in lasers in past two decades. Various hard tissue applications includes caries prevention, bleaching, restorative removal and curing, cavity preparation, dentinal hypersensitivity, growth modulation and for diagnostic purposes, whereas soft tissue application includes woun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…5 Various dental procedures can be done using diode laser through photodynamics or low-level laser therapy (LLLT). 6 Based on its clinical implications on tissue, a laser can broadly be classified as-soft tissue laser and hard tissue laser. 7,8 Soft tissue application of laser can be used for gingivectomy, gingivoplasty, gingival hyperplasia, operculectomy with minimal bleeding, enhancement of tooth eruption, aphthous lesions, herpes labialis, mucocele, frenectomy, ankyloglossia, pulp therapy, etc.…”
Section: Discussionmentioning
confidence: 99%
“…5 Various dental procedures can be done using diode laser through photodynamics or low-level laser therapy (LLLT). 6 Based on its clinical implications on tissue, a laser can broadly be classified as-soft tissue laser and hard tissue laser. 7,8 Soft tissue application of laser can be used for gingivectomy, gingivoplasty, gingival hyperplasia, operculectomy with minimal bleeding, enhancement of tooth eruption, aphthous lesions, herpes labialis, mucocele, frenectomy, ankyloglossia, pulp therapy, etc.…”
Section: Discussionmentioning
confidence: 99%
“…It provides a wide range of different types of effects on biological tissue, such as dissection, excision, resection, coagulation, and evaporation. Since CO 2 lasers absorb water, they generate a lot of heat, which creates a carbonized layer that serves as a biological dressing [40,41]. Laser surgery with this kind of lasers is an indication for the treatment of oral mucosal lesions, as it has a limited penetration depth of 0.2-0.3 mm.…”
Section: Co 2 Lasermentioning
confidence: 99%
“…Er:YAG laser can effectively cut or remove hard tissues of teeth, which is confirmed by the results of various studies. It can also be used in operations on soft tissues in cases where an apparent coagulation effect is not required [40,41]. Er:YAG laser radiation is well absorbed by structures with a high content of water and collagen, including soft tissues.…”
Section: Er:yag Lasermentioning
confidence: 99%
“…YAG lasers) and improvement of periodontal regeneration in animals and humans without damaging the surrounding bone and pulp tissues. (20) There is no doubt that specific protocols must be used to achieve specific goals. Aoki et al compared various power settings of an Er: YAG laser used for calculus removal in vitro and found that ablation of the tooth substance after laser scaling was generally observed within the cementum.…”
Section: Photobiomodulationmentioning
confidence: 99%